New insights into Andean evolution: An introduction to contributions from the 6th ISAG symposium (Barcelona, 2005) - Sempere, Thierry (2008)
The 6th International Symposium on Andean Geodynamics (ISAG) was held in Barcelona on September 12–14, 2005. Like previous editions, it provided an opportunity to some 250 scientists from most fields of the Earth Sciences to expose and discuss recent progresses in the understanding of the Andes. As much as 218 communications were presented (abstracts can be downloaded from manifesting that the interest of the geoscientific community for this outstanding orogen is not only high, but also growing. The prefaces to the Tectonophysics special issues published as sequels to the Oxford 1993 ISAG (Dewey and Lamb, 1996), Göttingen 1999 ISAG (Jaillard et al., 2002), and Toulouse 2002 ISAG (Gerbault and Hérail, 2005), reviewed the concepts, models and issues prevailing about the Andes. In the last years some views have started to evolve under the growing perception — and concern — that current models do not always reflect reality satisfactorily, especially in the Central Andes (e.g., Sempere, 2000; Wörner and Seyfried, 2001; Sempere et al., 2004; Hartley, 2005; Garzione et al., 2006; Sempere and Jacay, 2007). This situation somehow makes that some shifts in the dominant paradigm, which for this region is best illustrated by Isacks’s (1988) landmark paper, have to be expected in the forthcoming years. We therefore take the opportunity to review here some issues that are emerging.